Uterine Tumor Resembling Ovarian Sex Cord Tumors Type II with Vaginal Vault Recurrence - Oriana Marrucci; Paola Nicoletti; Alessandro Mauriello; Simone Facchetti; Lodovico Patrizi; Carlo Ticconi; Francesco Sesti; Emilio Piccione (Case Reports in Obstetrics and Gynecology)
UTROSCTs (Uterine Tumors Resembling Ovarian Sex Cord Tumors) are rare neoplasms of unknown etiology usually occurring in middle-aged women. Less than 100 cases of UTROSCT have been reported so far. Although the typical behavior of UTROSCT is benign, metastatic and recurrent cases can occur. Here we describe an extremely rare case of vaginal vault recurrence of UTROSCT occurring 5 years after total hysterectomy with bilateral salpingo-oophorectomy. Though rare, UTROSCT should always be taken into account in the differential diagnosis of uterine masses initially considered leiomyomas.